Exploring the Lived Experiences of Chronic Absenteeism Among Undergraduate Students at a Historically Black University: An Interpretative Phenomenological Analysis - Whitehead, Patrick; Leonhardt, Ronald; Mishoe, Malisha; Medlin, Dorene; Woodruff, Emily; Darrisaw, George (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This research examines chronic absenteeism at an American public, historically Black university. Chronic absenteeism, which became a problem during and following the COVID-19 pandemic, has contributed to rising failure rates and a 34% graduation-to-retention rate among students. Using the interpretative phenomenological analysis (IPA) method, the authors, who are college instructors, interviewed 13 students with histories of absenteeism. Student cases were analyzed separately and together to identify relevant absenteeism themes. Significant themes include life conflicts (such as a flat tire or illness), lack of perceived relevance of courses (such as courses that fall outside of a student’s major), and lack of course structure (such as inconsistent policies within a course). These barriers impact all students to some degree, and these obstacles have become more frequent and substantial post-COVID-19. The barriers are described using examples and recommendations, to mitigate the problems that include, among others, clear course policies of student support in syllabi. During course introductions, course time devoted to making clear, the items that are relevant to the students’ academic majors, and care taken to ensure correspondence between what is in the course schedule and what happens in class.